All Days 2004
DOI: 10.2118/89442-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Fluid Flow Through Single Fractures Using Experimental, Stochastic and Simulation Approaches

Abstract: A fracture is usually assumed as a set of smooth parallel plates separated by a constant width. However, the flow characteristics of an actual fracture surface would be quite different, affected by tortuosity and the impact of surface roughness. Though several researchers have discussed the effect of friction on flow, their efforts lack corroboration from experimental data and have not converged to form a unified methodology for studying flow on a rough fracture surface. In this study, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Similar, but more simplified, deformation procedures were performed for statistically derived aperture distributions (Pyrak-Nolte and Morris, 2000), profilometer measurements (Kim et al, 2003), laser-scan data (Nemoto et al, 2009;Watanabe et al, 2008Watanabe et al, , 2009) and a conceptual 2-D model (Liu et al, 2010). Furthermore, Dicman et al (2004) described changes in aperture distribution by combining laboratory data and stochastic approaches. Considering this study and further information provided in Table 1, most of the used fracture geometries can be assumed to be not directly correlated to the actual fracture geometries under loading conditions used for validation.…”
Section: Introductionmentioning
confidence: 99%
“…Similar, but more simplified, deformation procedures were performed for statistically derived aperture distributions (Pyrak-Nolte and Morris, 2000), profilometer measurements (Kim et al, 2003), laser-scan data (Nemoto et al, 2009;Watanabe et al, 2008Watanabe et al, , 2009) and a conceptual 2-D model (Liu et al, 2010). Furthermore, Dicman et al (2004) described changes in aperture distribution by combining laboratory data and stochastic approaches. Considering this study and further information provided in Table 1, most of the used fracture geometries can be assumed to be not directly correlated to the actual fracture geometries under loading conditions used for validation.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive review of flow though fractured media was reported by Berkowitz (2002). More recently, Oron and Berkowitz (1998), Dicman et al (2004) and Muralidharan et al (2004) studied flows through rough fractures. Lespinasse and Sausse (2000) studied the fluid flow in realistic fractures using a finite difference formulation.…”
Section: Introductionmentioning
confidence: 99%
“…We use the Probability density function of lognormal distribution that is expressed by the following equation [24][25][26] , and the relevant functions are shown in the below:…”
Section: The Flow Equation For Non-uniform Conductivity Hydraulic Fra...mentioning
confidence: 99%